Reduction of Tribocorrosion Products When Using the Platform-Switching Concept. (August 2018) - Alrabeah, G.O.; Knowles, J.C.; Petridis, H.
The reduced marginal bone loss observed when using the platform-switching concept may be the result of reduced amounts of tribocorrosion products released to the peri-implant tissues. Therefore, the purpose of this study was to compare the tribocorrosion product release from various platform-matched and platform-switched implant-abutment couplings under cyclic loading. Forty-eight titanium implants were coupled with pure titanium, gold alloy, cobalt-chrome alloy, and zirconia abutments forming either platform-switched or platform-matched groups ( n = 6). The specimens were subjected to cyclic occlusal forces in a wet acidic environment for 24 h followed by static aqueous immersion for 6 d. The amount of metal ions released was measured using inductively coupled plasma mass spectrometry. Microscopic evaluations were performed pre- and postimmersion under scanning electron microscope (SEM) equipped with energy-dispersive spectroscopy X-ray for corrosion assessment at the interface and wear particle characterization. All platform-switched groups showed less metal ion release compared with their platform-matched counterparts within each abutment material group ( P < 0.001). Implants connected to platform-matched cobalt-chrome abutments demonstrated the highest total mean metal ion release (218 ppb), while the least total mean ion release (11 ppb) was observed in the implants connected to platform-switched titanium abutments ( P ≤ 0.001). Titanium was released from all test groups, with its highest mean release (108 ppb) observed in the implants connected to platform-matched gold abutments ( P < 0.001). SEM images showed surface tribocorrosion features such as pitting and bands of fretting scars. Wear particles were mostly titanium, ranging from submicron to 48 µm in length. The platform-matched groups demonstrated a higher amount of metal ion release and more surface damage. These findings highlight the positive effect of the platform-switching concept in the reduction of tribocorrosion products released from dental implants, which consequently may minimize the adverse tissue reactions that lead to peri-implant bone loss.